Growth, nodulation and nitrogen fixation of cowpea in soils amended with composted tannery sludge - Santos, Joseany Andrade; Pinheiro Leal Nunes, Luis Alfredo; de Melo, Wanderley Jose [UNESP]; do Vale Figueiredo, Marcia Barreto; Singh, Rajeev Pratap; Carvalho Bezerra, Antonio Aecio; Ferreira de Araujo, Ademir Sergio (Sociedade Brasileira de Ciência do Solo, 2011)
Tannery wastes generation is increasing every year and a suitable method for tannery sludge management is necessary in order to decrease this environmental problem. The composting is recognized as a suitable method for sludge recycling.. The effect of tannery sludge compost (TSC) rates on growth, nodulation and N fixation of cowpea was investigated. Sandy and clayey soils were amended with TSC at rates of 0, 7.5, 15, 30, and 60 t ha(-1). The shoot dry weight of cowpea plants 45 days after emergence (DAE) was greater in the TSC-amended than in the unamended soil. In the sandy soil, nodule dry weight increased with TSC application 45 DAE. In the clayey soil, 45 DAE, nodule dry weight decreased with TSC amendment levels greater than 7.5 t ha(-1) compared to the unamended control. The application of TSC increased N accumulation in the cowpea plants. The results suggest that cowpea responds differently to TSC depending on the amendment rate and initial soil type.
Crescimento, nodulação e fixação de nitrogênio pelo feijão-caupi em solo com composto de lodo de curtume
Keywords: Waste; soil texture; Composting; Heavy metal